# Solve for y 4x+6y=32 4x+6y=32
Subtract 4x from both sides of the equation.
6y=32-4x
Divide each term by 6 and simplify.
Divide each term in 6y=32-4x by 6.
6y6=326+-4×6
Cancel the common factor of 6.
Cancel the common factor.
6y6=326+-4×6
Divide y by 1.
y=326+-4×6
y=326+-4×6
Simplify each term.
Cancel the common factor of 32 and 6.
Factor 2 out of 32.
y=2(16)6+-4×6
Cancel the common factors.
Factor 2 out of 6.
y=2⋅162⋅3+-4×6
Cancel the common factor.
y=2⋅162⋅3+-4×6
Rewrite the expression.
y=163+-4×6
y=163+-4×6
y=163+-4×6
Cancel the common factor of -4 and 6.
Factor 2 out of -4x.
y=163+2(-2x)6
Cancel the common factors.
Factor 2 out of 6.
y=163+2(-2x)2(3)
Cancel the common factor.
y=163+2(-2x)2⋅3
Rewrite the expression.
y=163+-2×3
y=163+-2×3
y=163+-2×3
Move the negative in front of the fraction.
y=163-2×3
y=163-2×3
y=163-2×3
Solve for y 4x+6y=32

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top